Historiophobia or the Enslavement of History: The Role of the 1948 Ethnic Cleansing in the Contemporary Peace Process - Ilan Pappe (Arab Studies Quarterly, 2016)
This article examines closely the role of the 1948 Palestinian catastrophe in the contemporary peace process. It argues that peace mediation in the conflict regarded history in general an obstacle for progress and the Palestinian victimization in 1948 as a marginal and irrelevant issue. This peace process, which ignored the ethnic cleansing of Palestine in 1948 and its impact on the contemporary reality, failed dismally. The article argues that only a courageous encounter with the crime committed in 1948 and an authentic search for rectifying it through restitutive justice, and not retribution, can open up a genuine process of reconciliation in Palestine.